Pullulan microneedle patches for the efficient transdermal administration of insulin envisioning diabetes treatment. (1st August 2020) - Fonseca, Daniela F.S.; Costa, Paulo C.; Almeida, Isabel F.; Dias-Pereira, Patrícia; Correia-Sá, Inês; Bastos, Verónica; Oliveira, Helena; Duarte-Araújo, Margarida; Morato, Manuela; Vilela, Carla; Silvestre, Armando J.D.; Freire, Carmen S.R.
Graphical abstract: Highlights: Dissolvable pullulan microneedles were successfully prepared by solvent casting. Pullulan-insulin microneedles successfully penetrate through the skin. Storage at 4, 20 and 40 °C maintained the secondary structure of insulin. Pullulan microneedles deliver 87% of insulin, 120 min after insertion. Pullulan-insulin microneedles are non-cytotoxic towards human keratinocyte cells. Abstract: The present study reports the fabrication of dissolvable microneedle (MN) patches using pullulan (PL), a water-soluble polysaccharide with excellent film-forming ability, for the transdermal administration of insulin, envisioning the non-invasive treatment of diabetes. PL MNs patches were successfully prepared by micromoulding and revealed good thermal stability (Tdmax  = 294 °C) and mechanical properties (>0.15 N needle −1 ), penetrating skin up to 381 μm depth, as revealed by in vitro skin tests. After application into human abdominal skin in vitro, the MNs dissolved within 2 h releasing up to 87% of insulin. When stored at 4, 20 and 40 °C for 4 weeks, insulin was able to retain its secondary structure, as shown by circular dichroism spectropolarimetry. The prepared PL MNs were non-cytotoxic towards human keratinocytes, being suitable for skin application. These findings suggest that PL MNs have potential to deliver insulin transdermally, thus avoiding its subcutaneous administration.